Patient-Specific Pluripotent Stem Cells in Neurological Diseases - Serpen Durnaoglu; Sermin Genc; Kursad Genc (Stem Cells International)
Many human neurological diseases are not currently curable and result in devastating neurologic sequelae. The increasing availability of induced pluripotent stem cells (iPSCs) derived from adult human somatic cells provides new prospects for cellreplacement strategies and disease-related basic research in a broad spectrum of human neurologic diseases. Patient-specific iPSC-based modeling of neurogenetic and neurodegenerative diseases is an emerging efficient tool for in vitro modeling to understand disease and to screen for genes and drugs that modify the disease process. With the exponential increase in iPSC research in recent years, human iPSCs have been successfully derived with different technologies and from various cell types. Although there remain a great deal to learn about patient-specific iPSC safety, the reprogramming mechanisms, better ways to direct a specific reprogramming, ideal cell source for cellular grafts, and the mechanisms by which transplanted stem cells lead to an enhanced functional recovery and structural reorganization, the discovery of the therapeutic potential of iPSCs offers new opportunities for the treatment of incurable neurologic diseases. However, iPSC-based therapeutic strategies need to be thoroughly evaluated in preclinical animal models of neurological diseases before they can be applied in a clinical setting.